Induced Ablation of Ghrelin Cells in Adult Mice Does Not Decrease Food Intake, Body Weight, or Response to High Fat Diet - McFarlane, Matthew R. (2014)
Injection of the peptide hormone ghrelin stimulates food intake in mice and humans. However, mice born without ghrelin demonstrate no significant loss of appetite. This paradox suggests either that compensation develops in mice born without ghrelin or that ghrelin is not essential for appetite control. To distinguish these possibilities, we generated transgenic mice (Ghrl-DTR) that express the diphtheria toxin receptor in ghrelin-secreting cells. Injection of diphtheria toxin in adulthood ablated ghrelin cells and reduced plasma ghrelin by 80-95%. Ghrelin cell-ablated mice exhibited no loss of appetite or body weight and no resistance to a high fat diet. To stimulate food intake in mice by ghrelin injection, we had to raise plasma levels many-fold above normal. Like germline ghrelin-deficient mice, the ghrelin cell-ablated mice developed profound hypoglycemia when subjected to prolonged calorie restriction, confirming that ghrelin acts to maintain blood glucose under famine conditions.